A newly developed low-cost 3D acoustic positioning system: Description and application in a reverberation room. (March 2020) - Guidorzi, Paolo; Pompoli, Francesco; Bonfiglio, Paolo; Garai, Massimo
Abstract: A newly developed low-cost 3D acoustic positioning system is used to measure the sound field inside a reverberation room. The measurement system requires a personal computer, a standard multi-channel sound card and very few external components such as 4 small amplified loudspeakers (used only for the 3D positioning system) placed at known fixed positions and a microphone, used as probe for both the positioning and the sound field measurements. A dodecahedron is used to excite the reverberation room with an MLS signal. The measurement is performed moving the microphone inside the reverberation room and measuring, point by point, the local impulse response, in order to analyze the room modes and possibly compute a spatially localized reverberation time. The results of the measurements are compared with a FEM model of the sound field inside the reverberation room.